Pengaruh Likuiditas, Leverage, dan Profitabilitas terhadap Keputusan Hedging Perusahaan BUMN di Bursa Efek Indonesia Periode 2019-2021 - Mustofa, Wahyu Amin; Ariani, Kurnia Rina (Masyarakat Ekonomi Syariah Bogor, 2024)
This research focuses on the financial distress hypothesis. This research shows that protecting against risk through hedging activities can reduce the possibility of financial distress which leads to company bankruptcy, which is a condition where the company's operations cannot run well because it experiences significant financial difficulties. serious (Irfan & Tri, 2014). This research is explanatory in nature, investigating the influence of independent variables on the dependent variable and formulating hypotheses to be tested. Liquidity as proxied by the current ratio has no significant effect on hedging decisions with a significance level of 0.070 > 0.05. Leverage as proxied by the debt to equity ratio has a significant effect on hedging decisions with a significance level of 0.033 < 0.05. Profitability as proxied by return on assets does not have a significant effect on hedging decisions with a significance level of 0.205 > 0.05.